Practical Digital Administration Instruction Addresses Technology Skill Gaps In Secondary Education: Pelatihan Instruksi Administrasi Digital Praktis Mengatasi Kesenjangan Keterampilan Teknologi Pendidikan Menengah - Muhammad Thariq; Hendra Sukmana; Diana Reza Andriani; Istiqomah Delia Nanda; Dwi Rahayu (Proceedings of The ICECRS, 2025)
General Background The digital era significantly transforms educational paradigms, necessitating robust technological competencies for active societal participation and future professional readiness. Specific Background Within Indonesia, secondary education frequently struggles with traditional instructional methods, access disparities, and inadequate infrastructure, which collectively restrict optimal technology utilization among learners. Knowledge Gap Although constructivist theories emphasize active knowledge building through practical interaction, a substantial discrepancy exists regarding how to practically integrate essential administrative software capabilities within secondary school environments. Aims This research analyzes a targeted internship initiative designed to develop practical software proficiencies among tenth-grade student council members at SMAN 1 Krembung Sidoarjo. Results Qualitative observations and thematic analyses reveal that direct mentoring in platform applications, specifically utilizing Canva and Google Sheets for website creation, certification, and attendance tracking, successfully builds functional digital capabilities, although infrastructural limitations and coordination challenges temporarily disrupted the learning process. Novelty This study specifically identifies student council organizations as strategic primary vehicles for peer-to-peer technological skill dissemination within resource-constrained public administration contexts. Implications Educational institutions must provide adequate learning facilities and continuously update instructional materials to include contemporary subjects such as artificial intelligence to sustain ongoing technological adaptation. Highlights: Direct mentoring utilizing accessible online design platforms successfully builds functional documentation and web creation capabilities for student organizations. Infrastructural limitations and team coordination challenges require immediate resolution to optimize institutional technology adaptation processes. Future instructional curriculums must incorporate artificial intelligence topics to maintain relevance with global technological advancements. Keywords: Digital Competence, Canva Application, Google Sheets, Constructivist Learning, Public Administration